An investigation on the value of intervals in Persian music - Sanati, Farshad (2020)
Theory of intervals in Persian music has a history of over 1000 years. Two influential theories regarding interval sizes have been proposed during the 20th century, first one by Ali Naqi Vaziri at the beginning of 20th century (1913) and the second one by Daryoush Talai at the end of 20th century (1995), but still the exact size of intervals is a matter of discussion between Persian musicians and theoreticians. This thesis investigates the possible similarities between the interval sizes found in theories and those used by Ney (Iranian classical flute) Players. The experiment stimuli are played by six Ney players which are categorized in 2 different groups, old and new generation. Players played pieces in all four main tetrachords in Persian music, namely Shur, Chahargah, Dashti and Mahoor. Exact amounts of pitches of each tetrachord were extracted using MIRtoolbox (an integrated set of functions written in Matlab); next size of intervals was calculated and compared with both theories. The analysis has shown that intervals played by the old generation are more correlated with old theory, while the new generation played intervals more correlated with the new theory. This study presents an interdisciplinary project involving musicology, ethnomusicology and music information retrieval. Most of the research in music information retrieval has been done on western classical music and working with non-western music is still an exploratory task and there is a great potential for future work in this domain.